2006
DOI: 10.1002/ijc.21799
|View full text |Cite
|
Sign up to set email alerts
|

Increased PTEN expression due to transcriptional activation of PPARγ by Lovastatin and Rosiglitazone

Abstract: Germline mutations in the tumor suppressor gene PTEN (protein phosphatase and tensin homolog located on chromosome ten) predispose to heritable breast cancer. The transcription factor PPARc has also been implicated as a tumor suppressor pertinent to a range of neoplasias, including breast cancer. A putative PPARc binding site in the PTEN promoter indicates that PPARc may regulate PTEN expression. We show here that the PPARc agonist Rosiglitazone, along with Lovastatin, induce PTEN in a dose-and time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 51 publications
4
95
0
2
Order By: Relevance
“…32,33 Recently, it has been shown that PTEN is a downstream target gene for PPARg, 34 and upregulation of PTEN by PPARg ligands such as rosiglitazone was probably responsible for the anticancer effects of these ligands. 35 Our in vitro study showed that rosiglitazone barely altered the expression of PTEN when XIAP is present, whereas this agent could significantly upregulate the expression of PTEN when XIAP was knocked out (HCT116-XIAP 2/2 cells). These results suggest that the presence of XIAP may be important in counteracting the effect of tumor suppressor PTEN.…”
Section: Discussionmentioning
confidence: 79%
“…32,33 Recently, it has been shown that PTEN is a downstream target gene for PPARg, 34 and upregulation of PTEN by PPARg ligands such as rosiglitazone was probably responsible for the anticancer effects of these ligands. 35 Our in vitro study showed that rosiglitazone barely altered the expression of PTEN when XIAP is present, whereas this agent could significantly upregulate the expression of PTEN when XIAP was knocked out (HCT116-XIAP 2/2 cells). These results suggest that the presence of XIAP may be important in counteracting the effect of tumor suppressor PTEN.…”
Section: Discussionmentioning
confidence: 79%
“…For example, a recent study suggests that the coactivator amplified-in-breast cancer 3 is needed for the (21). Studies from our own group also indicate that responsiveness to rosiglitazone requires at least one functional PTEN allele such that tumors with homozygous PTEN deletions or promoter mutations would prove refractory to treatment (22). Furthermore, signaling cross-talk between PPARg and estrogen receptor could lead to differential effects of PPARg ligand activation in breast cancer (23,24).…”
Section: Discussionmentioning
confidence: 98%
“…Because several reports have indicated that PTEN may be a downstream effector of PPAR␥ (Lee et al, 2006;Teresi et al, 2006), we assessed the effects of PPAR␥ on PTEN activity in H2122 cells. No consistent effect of PPAR␥ on PTEN expression was detected by immunoblotting.…”
Section: Ppar␥ Inhibits Lung Tumorigenesis By Inhibition Of Cox-2 713mentioning
confidence: 99%